Intertextuality and its meaning in Natan Zach's "Enosh keair yamav" (As for man, his days are as grass) - Shoham, Reʾuven 1938- (2006)
Natan Zach, a prominent subversive Israeli poet, began publishing his poetry in the mid-1950s, together with a group of young poets who felt obliged to transform Hebrew poetry. This group included poets and critics such as Moshe Dor, Arye Sivan, Yehuda Amichai, David Avidan, Gershon Shaked, and Benjamin Harshav (Hrushovski). They published their first poems and essays in Likra't (Toward), a journal that they founded, and their group took on the same name. Only four issues of the journal appeared between 1952 and 1954. Zach was one of the outstanding poets in this group. His first book of poetry, Shirim ri'shonim (Early Poems), was published in 1955. His second book, Shirim shonim (Diverse Poems, 1960), totally changed the Israeli canon in terms of its themes and its poetic texture.
Keywords: Humanity; Stanzas; Psalms; Irony; Literary Criticism; Romantic poetry; Modernist poetry; Oral poetry